2023
DOI: 10.1186/s42836-022-00158-z
|View full text |Cite
|
Sign up to set email alerts
|

Suction drainage in total knee replacement does not influence early functional outcomes or blood loss: a randomized control trial

Abstract: Introduction The use of wound drainage following total knee arthroplasty (TKA) remains controversial. The purpose of this study was to evaluate the impact of suction drainage on early postoperative outcomes in patients who underwent TKA with concomitant administration of intravenous tranexamic acid (TXA). Method One hundred forty-six patients undergoing primary TKA with systematic intravenous TXA were prospectively selected and randomly divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, patients without the drainage tube were more likely to experience blood stasis, tissue swelling, and blood extravasates. Anton et al 11 conducted a randomized controlled study on 146 patients 12 with total knee arthroplasty, and found no significant difference in blood loss, length of hospitalization, knee ROM, and KOOS score among patients with drainage tube placement. However, the value of a drainage tube after the UKA operation remains a controversy at present.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients without the drainage tube were more likely to experience blood stasis, tissue swelling, and blood extravasates. Anton et al 11 conducted a randomized controlled study on 146 patients 12 with total knee arthroplasty, and found no significant difference in blood loss, length of hospitalization, knee ROM, and KOOS score among patients with drainage tube placement. However, the value of a drainage tube after the UKA operation remains a controversy at present.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the average fall of hemoglobin levels in the group treated by TXA treatment without drainages was less compared to the other two groups (8.0%, 14.4% and 10.9%, respectively) 59 . Therefore, currently drainages appear to be not necessary when TXA is administered in selected orthopedic surgeries including proximal fractures of the femur 58 , 59 and knee arthroplasty 60 , 61 . However, as TXA in orthopedic and emergency trauma surgeries is still applied off-label in most cases, its use, particularly systemically, must for now be limited to indications where excessive bleeding is expected to lead to clinical complications, and contraindications such as an acquired or genetic increased risk for thromboembolic events must be taken into consideration carefully on a case-to-case basis.…”
Section: Clinical Usage and Efficacy Of Txamentioning
confidence: 99%
“…Conversely, the authors observed that drains were associated with a greater complication rate: infection and knee stiffness. Therefore, they concluded that the usage of a suction drain may not provide any benefit and may have adverse effects in the TKA procedure [6].…”
Section: Introductionmentioning
confidence: 99%